FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KONSUMEN TERHADAP LISTRIK PADA RUMAH TANGGA - Ezra Yunisa Nababan; Andhika Novester (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This research aims to determine the factors that influence the family's electrical energy demand. The research method used is descriptive quantitative, the data used is secondary data in the form of community income, population and economic growth. The results showed that income had a significant positive effect on household electrical energy demand, population had a significant positive effect on household electrical energy demand and economic growth had no effect on household electrical energy demand. Simultaneous test results show that all independent variables have an effect of 95.7% on household electrical energy demand.